2023
DOI: 10.1186/s12887-023-03855-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and non-pharmacological interventions in management of peripheral venipuncture-related pain: a randomized clinical trial

Abstract: Background Venipuncture is a routine nursing procedure in the pediatric ward for blood collection and transfusion. However, this procedure can cause severe pain and distress if not adequately managed. Methods Children aged 3–16 years old were randomized into three groups: EMLA group, distraction group, and combined group. The primary outcome was children’s self-reported pain scored using the Wong-Baker FACES® Pain Rating Scale. The parents-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Venipuncture is routine in pediatric patients' settings for blood collection and IV catheterizations [1], which can cause pain and fear [2,3]. According to Humphrey et al [4], A majority of children aged 7 to 12 who had their venipunctures reported feeling distressed during the process.…”
Section: Introductionmentioning
confidence: 99%
“…Venipuncture is routine in pediatric patients' settings for blood collection and IV catheterizations [1], which can cause pain and fear [2,3]. According to Humphrey et al [4], A majority of children aged 7 to 12 who had their venipunctures reported feeling distressed during the process.…”
Section: Introductionmentioning
confidence: 99%